ChemInform Abstract: Organomagnesium‐Catalyzed Isomerization of Terminal Alkynes to Allenes and Internal Alkynes. Issue 41 (October 2015) - Rochat, Raphael; Yamamoto, Koji; Lopez, Michael J.; Nagae, Haruki; Tsurugi, Hayato; Mashima, Kazushi
Abstract The synthesis of a dimeric organomagnesium complex (MGC) is reported.